2005
DOI: 10.1111/j.1439-0272.2005.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora of the low male genital tract in patients consulting for infertility

Abstract: The physiological aerobic bacterial flora of the low male genital tract was determined. This prospective study was performed on 600 semen specimens collected from 543 asymptomatic males consulting for infertility. Semen cultures were sterile in 28.8%, with a polymicrobial flora and/or absence or low titres of Ureaplasma urealyticum in 49.3%, and with one or two aerobic and facultative bacteria > or =1 x 10(3) CFU ml(-1) and/or U. urealyticum with titres > or =10(4) CCU ml(-1) (colour changing units) in 21.8%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 19 publications
2
42
0
4
Order By: Relevance
“…The fact that leukocyte count was lower in the positive group than in the negative group and below the normal reference of the WHO [10] confirms previous findings [7,9] that male genital colonization of G. vaginalis does not provoke an inflammatory response of leukocytes, in spite of the abundance of bacteria observed in infected men. According to previous reports, the prevalence of G. vaginalis in men who consulted infertility clinics varies from 9.6 to 44.2% [7,[11][12][13]16] .…”
Section: Gardnerella Vaginalis In Infertile Mensupporting
confidence: 76%
See 1 more Smart Citation
“…The fact that leukocyte count was lower in the positive group than in the negative group and below the normal reference of the WHO [10] confirms previous findings [7,9] that male genital colonization of G. vaginalis does not provoke an inflammatory response of leukocytes, in spite of the abundance of bacteria observed in infected men. According to previous reports, the prevalence of G. vaginalis in men who consulted infertility clinics varies from 9.6 to 44.2% [7,[11][12][13]16] .…”
Section: Gardnerella Vaginalis In Infertile Mensupporting
confidence: 76%
“…90%) can also be isolated in male urethra from men whose female partner has bacterial vaginosis [2] . Likewise, G. vaginalis has been cultured in men with cystitis [3] , prostatitis [4] and balanoposthitis [5] .Some studies have also shown that G. vaginalis colonizes semen from men attending infertility clinics, in rates that can reach 44% [6][7][8][9] . Due to seminal colonization and its association with male urogenital infections, it was thought that G. vaginalis might affect semen quality, causing infertility.…”
mentioning
confidence: 99%
“…Mycoplasma hominis is not considered part of normal bacterial flora. Rodin et al (11) suggested that asymptomatic multiple isolates from cultures should be considered as contaminants, and Virecoulon et al (15) indicated that a threshold ≥ 10 4 , instead of 10 3 , colonyforming units/mL is better for distinguishing infection from contamination. Additionally, Willén et al (17) found that the bacterial flora of the coronal sulcus and distal urethra are common sources of semen contamination (71%).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Virecoulon et al (15) suggested that in order to achieve sterile semen collection, cleansing of the lower urinary tract via urination after adequate water intake is required prior to semen collection. Also, patients in the Virecoulon study applied bactericidal and antifungal soap on their penis and rinsed it off with sterilised saline to minimise contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have been performed to confirm the involvement of bacterial infections, including Streptococcus, as one of the major reasons for male infertility [Swenson et al 1980;Virecoulon et al 2005;Kiessling et al 2008;Hou et al 2013]. Streptococcus agalactiae (Group B Streptococcus, GBS) is an important human pathogen causing severe urinary and male reproductive tract infections which may be responsible for male infertility [Mhalu 1977;Stropnik et al 1987;Szponar and Galiński 1993;Cunningham 2000;Rajagopal 2009;Fujita et al 2011].…”
Section: Introductionmentioning
confidence: 99%